Asia's new battlefield : the USA, China and the struggle for the Western Pacific - Heydarian, Richard Javad (Zed Books, 2015)
A timely and comprehensive guide to understanding territorial disputes in the Western Pacific and how the region's growing tensions could reconfigure the global order.